Improving Vocabulary Achievement of Young Learners Using Animated Video - S Syarifudin; M Muhammad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2018)
This study aims at finding out whether or not the use of video improves the learners’ vocabulary of the young learners. This study applied pre-experimental method with one group pre-test and post-test design. Twenty junior high school learners in Mataram involved in this study. The data were collected through vocabulary test (pre-test and post-test). This study used cluster random sampling technique. A t-test was used to measure the significance of animated video usage in improving young learners’ vocabulary achievement. Mean score of post-test was greater than the mean score of the pre-test. This study revealed that using animated video can improve learners’ vocabulary of the young learners